Scale Reliability Evaluation Under Multiple Assumption Violations. Issue 2 (3rd March 2016) - Raykov, Tenko; Marcoulides, George A.
Abstract : A latent variable modeling approach to evaluate scale reliability under realistic conditions in empirical behavioral and social research is discussed. The method provides point and interval estimation of reliability of multicomponent measuring instruments when several assumptions are violated. These assumptions include missing data, correlated errors, nonnormality, lack of unidimensionality, and data not missing at random. The procedure can be readily used to aid scale construction and development efforts in applied settings, and is illustrated using data from an educational study.